Front-turn movement in seoi-nage of elite judo athletes - Ishii, T.; Ae, M.; Kobayashi, Y.; Suzuki, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of our work was to investigate the control of the front-turn movement (Mae-mawari sabaki) for seoi-nage of elite judo athletes to obtain findings for effective coaching. Threedimensional data were collected on seoi-nage performed by six elite judo athletes using a three-dimensional motion analysis technique. The most distinguishing feature of the present study results is that the decrease in the trunk inclination angle closely related to the decrease in the moment of inertia of the body in the turning phase. This study found that elite judo athletes performed seoi-nage by turning their body while quickly raising their trunk so that the moment of inertia of the body about the vertical axis was minimized.